2021
DOI: 10.1007/978-3-030-66073-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Generation Gaps in LGBTQ+ Communities: Perspectives About Gay Neighborhoods Among Heteronormative and Homonormative Generational Cohorts

Abstract: Using Strauss-Howe generational theory as a guiding structure, this chapter examines differences between generational identity for LGBTQ+ individuals compared to heteronormative generational identity. We theorize that LGBTQ+ individuals may identify with two generational cohorts—one defined by birth year and a second related to “coming of age” as a sexual minority. A case study examining the lifespan of four LGBTQ+ celebrity personalities demonstrates the concept of generational layering. We argue “generationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Having no boundary on country or religious exposure has had an impact on the cohort's upbringing environment (Williams, 2015). Societal steps forward are combined with exposure to Black Lives Matter movements, increased terrorism, and LGBTQþ hate crime (Bitterman and Hess, 2020). This has meant Gen Z is very aware of real-world realities from a young age (Witt and Baird, 2018).…”
Section: Generation Z and Their Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having no boundary on country or religious exposure has had an impact on the cohort's upbringing environment (Williams, 2015). Societal steps forward are combined with exposure to Black Lives Matter movements, increased terrorism, and LGBTQþ hate crime (Bitterman and Hess, 2020). This has meant Gen Z is very aware of real-world realities from a young age (Witt and Baird, 2018).…”
Section: Generation Z and Their Characteristicsmentioning
confidence: 99%
“…Generational marketing theory highlights a timeline of generations relevant to marketing today (Bevan-Dye, 2020). The concept understands that each generation has unique expectations, experiences and generational history (Bitterman and Hess, 2020). These exposures contribute towards generations lifestyle and values that influence cohorts buying behaviours (Williams and Page, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This concurs with studies that have identified that being older is generally associated with more negative attitudes, and that acceptance of homosexuality increases as the age of respondents decreases [ 22 , 32 ]. However, it is necessary to analyze whether these associations are due to generational differences toward homosexuality rather than to the chronological age of the respondents [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…(…) And there were all kinds of people." Indeed, research shows that the gay scene has radically changed over the past decades, both in Belgium and abroad [15,34].…”
Section: It's Still Hardmentioning
confidence: 99%
“…Those coming of age in the 1970s witnessed the growth of the gay movement after the Stonewall riots in 1969, while those coming of age in the 1980s experienced the AIDS crisis as well as a new wave of stigmatization. Similarly, Bitterman and Hess [15] discuss LGBTQ generations as those coming of age in a similar period, such as the Baby Boom generation which came of age during the social revolutions of the 1960s, including sexual liberation. Elsewhere, Hammack et al [16] discuss the health consequences of social changes and important historical events in the life course of gay men, drawing attention in particular to their timing in relation to individual lives.…”
Section: Introductionmentioning
confidence: 99%